The neural basis of perceiving person interactions. (September 2015) - Quadflieg, Susanne; Gentile, Francesco; Rossion, Bruno
Abstract: This study examined whether the grouping of people into meaningful social scenes (e.g., two people having a chat ) impacts the basic perceptual analysis of each partaking individual. To explore this issue, we measured neural activity using functional magnetic resonance imaging (fMRI) while participants sex-categorized congruent as well as incongruent person dyads (i.e., two people interacting in a plausible or implausible manner). Incongruent person dyads elicited enhanced neural processing in several high-level visual areas dedicated to face and body encoding and in the posterior middle temporal gyrus compared to congruent person dyads. Incongruent and congruent person scenes were also successfully differentiated by a linear multivariate pattern classifier in the right fusiform body area and the left extrastriate body area. Finally, increases in the person scenes' meaningfulness as judged by independent observers was accompanied by enhanced activity in the bilateral posterior insula. These findings demonstrate that the processing of person scenes goes beyond a mere stimulus-bound encoding of their partaking agents, suggesting that changes in relations between agents affect their representation in category-selective regions of the visual cortex and beyond.